The Influence of Madrasah Principal’s Leadership Style and Teacher’s Job Satisfaction on Teacher’s Performance - Saputra, Yudi; Ahmad, Syarwani; Widayatsih, Tri (Journal of Social Work and Science Education, 2024)
This study aims to determine and analyze: (1) The relationship between the leadership style of the Madrasah principal and teacher performance; (2) The relationship between teacher job satisfaction and teacher performance; and (3) the relationship between the principal’s leadership style and teacher’s job satisfaction together with teacher performance. This research is a quantitative study using the partial correlation method. This research was conducted at Madrasah Tsnawiyah (MTs) throughout Gandus District with 95 teachers as respondents. Data collection techniques using questionnaires and documentation. The validity test uses construct validity, while the reliability test uses Cronbach’s Alpha. Prerequisite test analysis using the normality test, Linearity Test, and Multicollinearity Test, and data were analyzed using simple regression and multiple regression techniques. The results showed that: (1) there is a positive and significant relationship between the leadership style of the Madrasah head and teacher performance with a correlation value of 0,937 with a percentage of relationship of 87,8% while 12,2% is determined by other factors not mentioned in this research.